Analysis Of The Prohibition Of Providing Compensation To Foundation Board Members From An Islamic Justice Perspective - Mohammad Yudithama Al Kautsar; Wahyu Dwi Agung Priyo Susila; Azwar Azwar; Bayu Taufiq Possumah (Green Publisher Indonesia, 2024)
This research aims to analyze the prohibition on giving wages to foundation organs (founders and trustees) from an Islamic perspective, especially on the principles of justice. This research is included in the type of qualitative descriptive research (non-statistical) using the library research method (literature review) through a juridical-normative and conceptual approach. The results of the research show that from an Islamic perspective, the prohibition on giving salaries or wages to foundation organs, especially to foundation Trustees and Supervisors, can be said to be a form of injustice, where the management (with some limitations) is entitled to a salary, while the Trustees and Supervisors are not allowed to receive it. Therefore, when the administrators and related parties in the management of the foundation, including Trustees and Supervisors, work in accordance with a mutually agreed contract, agreement, or contract, then wages for performance must be paid fairly and transparently, according to the agreement and willingness of both parties.